Definition of concrete and composite precast concrete pavements texture - Vaitkus, Audrius; Andriejauskas, Tadas; Šernas, Ovidijus; Čygas, Donatas; Laurinavičius, Alfredas (Transport, 2019)
In the context of increasing traffic demands and emerging mobility trends road infrastructure has to shift towards the fifth generation of roads, which according to Forever Open Road (FOR) vision are envisioned as adaptable to traffic volumes, resilient to changing weather conditions, quickly built, effectively maintained, suitable for retrofitting, self-monitoring, self-repairing and recyclable. Concrete modular pavements can be defined as an example of such type of road infrastructure. Functional needs are mainly associated with implementation area/location, traffic and mobility demands, environmental constraints and etc. This also has a significant impact on the selection of Precast Concrete Pavements (PCP) texture formation method and materials. Concrete pavement surface texture affects both safety and tyre/road noise characteristics. Exposed Aggregate Concrete (EAC) and porous concrete are the most suitable noise reducing solutions for highways and streets wearing layer even in severe traffic and climate conditions. According to the literature analysis, the algorithm of highways and streets low noise concrete design was created. It is recommended to use the highest quality aggregates with maximum size up to 8 mm, gap-graded gradation, higher amount of cement and lower water/cement ratio. The most important characteristics of EAC are Mean Profile Depth (MPD), Mean Texture Depth (MTD) and profile count, while the most important characteristics of porous concrete are compressive strength, outflow and air void content.